Agricultural value chains in a fragile state: The case of rice in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
Nearly one-quarter of the global population lives in fragile states. Yet, despite the enormous importance of these areas for reducing global poverty and food insecurity, there is relatively little research examining how agricultural value chains, crucial for assuring food security, respond and adapt to such contexts. This paper analyzes Myanmar’s rice value chain–its most important staple crop and largest value chain–during the economic collapse and political instability caused by a military coup in early 2021. It relies on unique data collected with a large sample of rice retailers and millers before and after the coup. Despite many challenges in the rice value chain after the coup, such as banking and transport, rice processing and trade continued, assuring availability of rice in most retail markets and illustrating the resilience of the value chain to a major shock. While processing margins were mostly stable, an increased distribution margin (between rice millers and retailers) led to 11 percent higher average retail prices after the coup, implying welfare costs of almost USD 500 million. Using a market-pair regression method, we find that localized violence near sellers and buyers, distances traveled, and distance of vendors from international borders are associated with significantly increased rice price dispersion between rice retailers and mills. Despite the amalgam of problems to address in such settings, prioritizing the easing of transport restrictions, stabilizing fuel prices, and facilitating safe spatial arbitrage of food products would likely help prevent further food price inflation, assure higher farm prices, and improve welfare.